Alisertib plus induction chemotherapy in previously untreated patients with high-risk, acute myeloid leukaemia: a single-arm, phase 2 trial. Issue 2 (February 2020) - Brunner, Andrew M; Blonquist, Traci M; DeAngelo, Daniel J; McMasters, Malgorzata; Fell, Geoffrey; Hermance, Nicole M; Winer, Eric S; Lindsley, R Coleman; Hobbs, Gabriela S; Amrein, Philip C; Hock, Hanno R; Steensma, David P; et al.
Summary: Background: Increased aurora A kinase (AAK) expression occurs in acute myeloid leukaemia; AAK inhibition is a promising therapeutic target in this disease. We therefore aimed to assess the activity of alisertib combined with 7 + 3 induction chemotherapy in previously untreated patients with high-risk acute myeloid leukaemia. Methods: We did a single-arm, phase 2 trial of patients recruited from the Dana–Farber/Harvard Cancer Center in the USA. Eligible patients had previously untreated acute myeloid leukaemia, an Eastern Cooperative Oncology Group performance status of 0–2, and were at high risk of disease as defined by the presence of an adverse-risk karyotype, the presence of secondary acute myeloid leukaemia arising from previous myelodysplastic syndrome or myeloproliferative neoplasm, the presence of therapy-related acute myeloid leukaemia, or being 65 years or older. Enrolled patients received 7 + 3 induction chemotherapy of continuous infusion of cytarabine (100 mg/m 2 per day on days 1–7) and intravenous bolus of idarubicin (12 mg/m 2 per day on days 1–3). Oral alisertib (30 mg) was given twice per day on days 8–15. Patients could receive up to four consolidation cycles with cytarabine and alisertib, and alisertib maintenance for 12 months. The primary endpoint was a composite including the proportion of patients achieving complete remission and those with a complete remission with incomplete neutrophil or platelet count recovery. Analyses were per-protocol. This study is registered with Clinicaltrials.gov, number NCT02560025, and has completed enrolment. Findings: Between Dec 31, 2015, and Aug 1, 2017, we enrolled a total of 39 eligible patients. 19 (49%) of 39 patients had secondary acute myeloid leukaemia and three (8%) had therapy-related acute myeloid leukaemia. At mid-induction, 33 (85%) of 39 patients showed marrow aplasia, six (15%) received re-induction. The median follow-up was 13·7 months (IQR 12·7–14·4). Composite remission was 64% (two-stage 95% CI 48–79), with 20 (51%) of 39 patients achieving complete remission and five (13%) achieving complete remission with incomplete neutrophil or platelet count recovery. The most common grade 3 or 4 adverse events included febrile neutropenia (16 [41%] of 39), neutropenia (12 [31%]), thrombocytopenia (13 [33%]), anaemia (11 [28%]), anorexia (nine [23%]), and oral mucositis (four [10%]). No treatment-related deaths were observed. Interpretation: These results suggest that alisertib combined with induction chemotherapy is active and safe in previously untreated patients with high-risk acute myeloid leukaemia. This study met criteria to move forward to a future randomised trial. Funding: Millennium Pharmaceuticals.